Maksimalkan Keunggulan Daya Saing Melalui Peran Strategis SDM Hotel Bintang Tiga: Studi Kasus Hotel Ameera Pekanbaru - Siti Labibah, Ana; Purnama, Intan; Suraya, Nur; Wulandari, Shevia; Riofita, Hendra (CV. Lafadz Jaya, 2024)
The role of strategic human resource management is the main key in changing company management to achieve competitive advantage. To make this happen, the Human Resources Manager (HR Manager) must be able to carry out the strategic role of HR and provide added value to the company so that competitive advantage can be achieved. However, not many new HR Manager roles have been implemented by mid-level companies, let alone small companies. This research was conducted with the aim of knowing and identifying the strategic role of HR Managers in anticipating current business competition, the strategic role of HR Managers, and using HR as a factor to create a company's competitive advantage. This research was conducted using qualitative methods in the mid-level hotel industry in the city of Pekanbaru. The underlying philosophical assumption is positivist. The data collection technique uses semi-structured interviews. Data analysis uses coding with NVivo International 10 software. The themes used are the role of the HR Manager in contributing to business competition and the strategic role of the HR Manager in creating the company's competitive advantage which is analyzed based on the number of coding references. The result was that there were three participants who had carried out strategic HR roles. Meanwhile, the HR theme as a factor in achieving a company's competitive advantage is analyzed based on a text search query which produces a word tree. The result is that HR is used as a factor to achieve the company's competitive advantage.